Analysis of construction parameters of outriggers in the mega column-core tube-outrigger structure based on seismic reliability. (June 2022) - Wang, Tianlong; Zhang, Xun'an; Yang, Shixuan; Wang, Xinwei
Abstract: The design of outriggers is one of the hot issues in mega column-core tube-outrigger structures (MCCTOS). Therefore, the analysis of the parameters of the outriggers is of great practical significance. In this paper, based on the generalized probability density evolution theory, the reliabilities of MCCTOS with different outrigger parameters are investigated by absorbing boundary condition method and extreme-value distribution method, respectively. Based on the consideration of the randomness of the structural parameters and earthquake, the influence of the linear bending stiffness ratio of the outrigger-to-core tube, the number and position of the outriggers on the MCCTOS are analyzed by quantitative reliability. By comparing the results, it is found that for one-outrigger structure and two-outrigger structure, the reliability of the structure will reach a stable stage when the linear bending stiffness ratio of the outrigger-to-core tube is taken as 0.5 and 0.7 respectively. It indicates that the difference in the number of outriggers leads to the different reasonable values of the linear bending stiffness ratio of the outrigger-to-core tube. In addition, the reasonable locations of the outriggers can maximize the overall reliability of the structure and make the distribution of the reliability of each storey more uniform. The analysis of construction parameters of outriggers from the perspective of reliability can more comprehensively describe the influence of outriggers on the seismic capacity of the structure. The investigation on the seismic reliability of MCCTOS can more objectively evaluate the safety of structure. Moreover, the analysis of different construction parameters of outriggers in the MCCTOS based on seismic reliability can provide more objective suggestions for the design of outriggers.